2010
DOI: 10.2353/ajpath.2010.081127
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme N-Terminal Inactivation Alleviates Bleomycin-Induced Lung Injury

Abstract: Bleomycin has potent anti-oncogenic properties for several neoplasms, but drug administration is limited by bleomycin-induced lung fibrosis. Inhibition of the renin-angiotensin system has been suggested to decrease bleomycin toxicity, but the efficacy of such strategies remains uncertain and somewhat contradictory. Our hypothesis is that, besides angiotensin II, other substrates of angiotensin-converting enzyme (ACE), such as the tetrapeptide N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP), play a significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…Accordingly, Zuo and colleagues showed that Ac-SDKP has anti-fibrotic effects in both early and late stages of renal fibrosis induced by unilateral ureteral obstruction whereas Tβ4 alone has context- and time-dependent effects on renal fibrosis [9]. Furthermore, the current results are in agreement with observations of a previously published study showing that accumulation of endogenous Ac-SDKP in ACE N-terminal catalytic site-KO mice alleviates BLEO-induced lung injury, in particular fibrosis [19]. Similarly, exogenous Ac-SDKP has been shown to inhibit pulmonary fibrosis in rats with SiO2-induced silicosis [10, 11].…”
Section: Discussionsupporting
confidence: 89%
“…Accordingly, Zuo and colleagues showed that Ac-SDKP has anti-fibrotic effects in both early and late stages of renal fibrosis induced by unilateral ureteral obstruction whereas Tβ4 alone has context- and time-dependent effects on renal fibrosis [9]. Furthermore, the current results are in agreement with observations of a previously published study showing that accumulation of endogenous Ac-SDKP in ACE N-terminal catalytic site-KO mice alleviates BLEO-induced lung injury, in particular fibrosis [19]. Similarly, exogenous Ac-SDKP has been shown to inhibit pulmonary fibrosis in rats with SiO2-induced silicosis [10, 11].…”
Section: Discussionsupporting
confidence: 89%
“…To address this, we studied N-KO mice treated with angiotensin II in which POP activity was blocked by daily S-17092 injection, but in which AcSDKP levels were increased by minipump infusion of 1.5 mg/kg/day of peptide, a dose consistent with previous studies. 19 These mice were compared to equivalent N-KO mice treated with angiotensin II and S-17092 but without AcSDKP supplementation (Fig. 6).…”
Section: Resultsmentioning
confidence: 99%
“…6 We treated N-KO mice with S-17092 using conditions previously shown to reduce plasma AcSDKP levels to WT levels. 19 With POP inhibition, N-KO macrophage production of TNFα in response to LPS was restored to WT levels. Further, POP inhibition reduced the angiotensin II-mediated elevation of blood pressure in N-KO mice to the levels seen in WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using ex vivo human lung fibroblasts treated with TGF-b, we have investigated the properties of Tb4 and the peptide derived from its aminoterminal end, N-acetyl-serylaspartyl-lysyl-proline (Ac-SDKP). Ac-SDKP was implicated in the mechanism of protection from bleomycin-induced lung injury achieved by ACE N-terminal genetic inactivation [9], and it was shown to mediate the antifibrogenic effects of ACE inhibitors on both heart and kidney fibrosis [10,11] and to inhibit pulmonary inflammation and fibrosis in SiO 2 -induced silicosis [12,13].…”
Section: Introductionmentioning
confidence: 99%